1984
DOI: 10.2165/00003088-198409010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Tinidazole Pharmacokinetics in Severe Renal Failure

Abstract: The single-dose pharmacokinetics of intravenously and orally administered tinidazole were studied in normal subjects and patients with severe chronic renal failure. The clearance of tinidazole was also measured in patients on regular haemodialysis. After intravenous administration the mean elimination half-life of tinidazole was 17.1 +/- 2.3 (SD) hours in the normal subjects and 16.9 +/- 4.9 hours in patients with renal failure; the mean apparent volumes of distribution were 0.80 +/- 0.09 L/kg and 0.69 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It is unlikely that renal dysfunction will significantly alter the pharmacokinetics of the drug (Wood et al 1982). The pharmacokinetics of intravenous and oral tinidazole have been evaluated in patients with severe renal failure (Robson et al 1984). Following either route of administration, no differences were seen in elimination t,;, when compared with a control group of volunteers and no accumulation of the 2-hydroxymethyl metabolite was seen in either group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that renal dysfunction will significantly alter the pharmacokinetics of the drug (Wood et al 1982). The pharmacokinetics of intravenous and oral tinidazole have been evaluated in patients with severe renal failure (Robson et al 1984). Following either route of administration, no differences were seen in elimination t,;, when compared with a control group of volunteers and no accumulation of the 2-hydroxymethyl metabolite was seen in either group.…”
mentioning
confidence: 99%
“…Haemodialysis removed approximately 40% of the drug following a 6h session using a twin coil dialyser (Flouvat et al 1983). It has been suggested that a full or half dose of the drug be administered after dialysis (Flouvat et al 1983;Robson et al 1984).…”
mentioning
confidence: 99%
“…The observed half-life of tinidazole in plasma was about 17 h, which was slighty longer than that reported by others; the published values have ranged from 12 to over 16 h [14][15][16][17][18]. Tinidazole was observed to persist slighty longer in blister fluid than in plasma, but the differences were statistically insignificant; the average half-lives were about 19 and 17 h, respectively.…”
Section: Resultsmentioning
confidence: 74%
“…5. Since not all samples of blister fluid were taken, the ratio of the con- [15][16][17]. As far as is known, there is no information about the penetration of the drug into cantharidin-induced skin blister fluid.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigating the plasma pharmacokinetics of DEC in patients with moderate and severe renal impairment could be identified (Table 3). (µg h/mL) [15] Diethylcarbamazine can be used for the treatment of different filarial diseases, such as lymphatic filariasis, loiasis, tropical pulmonary eosinophilia, and onchocerciasis. No tissue PK studies could be identified that met our requirements, except for one study that investigated the penetration of DEC into saliva (Table 2).…”
Section: Diethylcarbamazinementioning
confidence: 99%